Army In the Civil War : Chancellorsville and Gettysburg. - Doubleday, Abner (Digital Scanning, Incorporated, Ebrary, Incorporated [distributor], 2001)
This extensive 16-volume set presents subjects surrounding the Civil War. Written by 14 different authors such as Abner Doubleday and John Nicolay, it is separated into two points of view, the Army and the Navy. The Army's thirteen volumes cover events and battles from the “Outbreak of Rebellion” to “Chancellorsville and Gettysburg” and on to “The Virginia Campaign of ‘64 and ‘65”. A volume of statistical records completes the Army's set. The 3 volumes about the Navy during the Civil War include “The Blockade and the Cruisers”, “The Atlantic Coast” and “The Gulf and Inland Waters”. Each volume holds a wealth of information, with its own introduction, preface, index, appendix(s), illustrations and maps. As a set, it is an in-depth view of this time in American history.